KOMUNIKASI KESEHATAN BINA KELUARGA REMAJA DALAM EDUKASI GAYA HIDUP SEHAT KELUARGA DI DESA SUNGAI BULUH SINGINGI HILIR - Rahmita Dewi; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Bina Keluarga Remaja (BKR) is a work program of the National Family Planning Population Agency (BKKBN) called Planning Generation ( GenRe ). Bina Keluarga Remaja at Sungai Buluh village was inaugurated at the beginning of the year 2018. The establishment of the BKR was due to the emergence of awareness about the problems of teens that occurred in society such as smoking and drug abuse and the importance of education for families in order to produce quality teenagers as the next generation of the nation. The purpose of the study this is to determine the form of communication of health, methods of persuasion communication of health and patterns of communication of health were conducted by “Bina Keluarga Remaja” in education style of living healthy family in the village of Sungai Buluh Singingi Hilir. This study using the methods of qualitative with descriptive approach, techniques of collecting data is through observation, interviews, and documentation with the number of informants totalling 8 people accordingly with the criteria that have been determined through the technique of purposive is BKR chairman, BKR Secretary, Chairman of the PKK, and BKR Participant activity. Mechanical analysis of the data in the study is that using the model of Miles and Huberman and technical examination of the validity of the data that is an extension of participation and triangulation. Results of the study showed that in the communication of health were conducted by Bina Keluarga Remaja at Sungai Buluh Village are : First : The form of communication of health that is applied by Bina Keluarga Remaja at Sungai Buluh village this there are four : Interpersonal health Communication, Health Group Communication, Health Organization Communications, and Communication Health Media . Secondly :  methods of persuasion are used in the delivery of information to the public consists of three kinds, namely activities of education, counseling, and therapy Pattern Relief God  for Emotional Freedom Technique (EFT PPA). Third : the pattern of communication that is used is the pattern of communication two directions. As for the method of persuasion the most dominant use in the activities is the extension that is supported by the credibility of the communicator. Keywords: Communication of health, family education, bina keluarga remaja